The impact of Cymbopogon martinii essential oil on Cutibacterium (formerly Propionibacterium) acnes strains and its interaction with keratinocytes - Murbach Teles Andrade, Bruna Fernanda [UNESP]; Nunes Barbosa, Lidiane; Bérgamo Alves, Fernanda Cristina [UNESP]; Pereira Marques, Ana Flávia [UNESP]; Albano, Mariana [UNESP]; Mores Rall, Vera Lúcia [UNESP]; Brüggemann, Holger; Fernandes Júnior, Ary [UNESP] (Oxford University Press (OUP), 2018)
Objectives: The human skin microbiota is mainly composed of bacteria belonging to the genera Staphylococcus, Cutibacterium, Micrococcus and Corynebacterium, but on the skin of the face and back, ca. 50% of the total microbiota is represented by the bacterium Cutibacterium acnes. The aim of this research was to evaluate the impact of C. martini EO and its major compound, geraniol, on C. acnes. Methods: The minimum inhibitory concentration against C. acnes strains, phenotypic changes and responses of the proteome was determined. In addition, was assessed the effect of compounds in RNA-binding assay, on C. acnes-exposed keratinocytes and on the C. acnes type distribution on shoulder skin. Key findings: The range of the MIC was 0.7 to 1.6 mg/ml for the three main C. acnes types. There were no cytotoxic effects of compounds in the absence or presence of C. acnes; after 7 days of exposure to C. martini EO, we could not detect a major shift of the C. acnes types on shoulder skin that was found to be dominated by C. acnes strains of types II and IA2. Conclusions: Our work gives novel insight into the skin microbiota-interacting properties of C. martini EO.
Keywords: antibacterial activity; chemical characterization; Cutibacterium acnes; Cymbopogon martinii; keratinocytes